Reliability of Agricultural Tractors According to Polish Farmers - Karol Durczak (Tehnički Vjesnik, 2020)
The progressing digitisation of European and global agriculture requires a rational approach to the reliability of agricultural machinery and vehicles. It is not easy to access data on failures of their parts, units and systems, which are necessary for classic characterisation of reliability. For this reason, it is necessary to develop other unconventional methods of acquiring information about the technical condition of machinery and convert it into a numerical form. This study presents an original method of quantifying the relative index of reliability of farm tractors based on their owners' subjective opinions. At present the rankings obtained by means of this method are the only tool supporting purchase decisions in situations of uncertainty and risk. Polish farmers found Valtra tractors to be the most reliable. The average reliability index is 0.87. Among 12 brands in the ranking the users rated 11 specific reliability criteria of Valtra tractors the highest. The runner-up was John Deere-a global manufacturer of agricultural machinery and vehicles. The German brand Fendt was the third in the ranking.